Physics Teaching. Inclusion. Deaf Students. High School. (REMUNOM, 2025)
Teaching Physics to deaf students in high school presents specific challenges that require methodological adaptations and teaching resources aligned with the linguistic, cognitive, and cultural particularities of these students. In view of this, this article aims to conduct a systematic literature review (SLR) on teaching Physics to deaf students. For this purpose, the Google Scholar database was chosen and the time frame defined from 2020 to 2025 (last five years). For the systematic search, the following descriptors were used: "PHYSICS  TEACHING"  AND  "DEAF"  OR  "DEAF"  AND  "HEARING IMPAIRMENT" AND "INCLUSION", which resulted in the selection of twenty-one articles for analysis. In short, the conclusive results indicate that the construction of an inclusive education for the deaf requires an integrated approach that involves methodological innovation, respect for deaf culture, critical use of assistive technologies, and addressing the structural and formative challenges still present in schools. Such integration is essential for Physics teaching to fulfill its role in the critical, autonomous and civic education of all students. Thus, this study reinforces the importance of thinking of Physics teaching not only as the transmission of scientific content and concepts, but as a space for the construction of meanings that respects and welcomes the multiple forms of communication, learning and cultural expression.